Karakterisasi Bacillus cereus strain IrN yang memiliki sifat multiresistensi terhadap tembaga dan pewarna - Irawati, Wahyu; Lucky, Egilia; Tumakaka, Yovanka P.P; Immanuel, Charles; Marvella, Eunike Bunga (Jurnal Biologi Udayana; Vol 26 No 2 (2022): JURNAL BIOLOGI UDAYANADO - 10.24843/JBIOUNUD.2022.v26.i02.p10, 2022)
An increase in the activity of textile industries has increased the load waste disposal into the environment. Copper is a component of synthetic dyes used in textile industries, and therefore their wastes have potential to contain copper in addition to dyes. Bioremediation using indigenous bacteria with resistant to dyes and copper is expected to increase the efficiency of textile waste treatment. IrN bacterial isolate is an indigenous bacterium with resistant properties to copper. This bacterium was isolated from waste treatment. The main aims of this study were to identify the molecular characteristics and to investigate its resistance and ability to decolorize various dyes. Molecular identification of the isolate was carried out by sequencing its 16S rDNA gene. The medium used was Luria Bertani with the addition of dye and/or CuSO 4 as a treatment. There were 12 kinds of dyes used, namely: Methylene Blue, Malachite Green, Congo Red, Mordant Orange, Reactive Black, Direct Yellow, Basic Fuchsin, Reactive Orange, Disperse Orange, Remasol, Wantex Red, and Wantex Yellow. Decolorization ability and bacterial growth were measured using a spectrophotometer. The results of the 16S rDNA analysis showed that the IrN isolate were identified as Bacillus cereus with a similarity of 99.91%.  Strain IrN bacterial isolates had multi-resistance to 3 mM CuSO 4 , and all dyes were tested at a concentration of 200 ppm. However, at 500 ppm IrN was only resistant to methylene blue. IrN bacteria decolorized at 200 ppm and 500 ppm Methylene Blue by 42.78% and 38.1%, respectively. The addition of 3 mM CuSO 4 to 500 ppm Methylene Blue medium still enabled bacteria to decolorize Methylene Blue even though its decolorization ability decreased to 34.17%. IrN bacteria could also decolorize Malachite Green, Congo Red, and Basic Fuchsine with a maximum capacity of 98.16%, 70.29%, and 79.07% respectively.